Quantification of High‐Temperature Transition Al2O3 and Their Phase Transformations. Issue 48 (23rd September 2020) - Kovarik, Libor; Bowden, Mark; Andersen, Amity; Jaegers, Nicholas R.; Washton, Nancy; Szanyi, János
Abstract: High‐temperature treatment of γ‐Al2 O3 can lead to a series of polymorphic transformations, including the formation of δ‐Al2 O3 and θ‐Al2 O3 . Quantification of the microstructure in the range where δ‐ and θ‐Al2 O3 are formed represents a formidable challenge, as both phases accommodate a high degree of structural disorder. In this work, we explore the use of an XRD recursive‐stacking formalism for the quantification of high‐temperature transition aluminas. We formulate the recursive‐stacking methodology for modelling of disorder in δ‐Al2 O3 and twinning in θ‐Al2 O3 and show that explicitly accounting for the disorder is necessary to reliably model the XRD patterns of high‐temperature transition alumina. We also use the recursive stacking approach to study phase transformation during high‐temperature (1050 °C) treatment. We show that the two different intergrowth modes of δ‐Al2 O3 have different transformation characteristics and that a significant portion of δ‐Al2 O3 is stabilized with θ‐Al2 O3 even after prolonged high‐temperature exposures. Abstract : Quantification of the microstructure of transition aluminas represents a formidable challenge due to high degree of structural disorder. In this work, an XRD recursive‐stacking formalism is developed and used for the quantification of high‐temperature transition aluminas.